CURRICULARIZATION OF EXTENSION IN HIGHER EDUCATION: CASE ANALYSIS AND PRACTICES AT FAVENI UNIVERSITY CENTER - Machado, Débora Mendonça Monteiro; Rossi, Drieli Aparecida; de Lima, Francisco das Chagas Galvão; Lopes, Ricardo David; Rodrigues, Ana Paula; Zeferino, Vagner Aquino; Machado, Danilo Augusto de Souza (Seven Editora, 2025)
This study examines the implementation of extension curricularization in higher education, focusing on its implications for the academic and social development of students. Using the FAVENI University Center as a case study, the work analyzes the effectiveness of extension activities when integrated into the curriculum, promoting a comprehensive education that encompasses both theoretical development and social practice. The research was based on accessibility and nonverbal communication experiments, where students experienced common barriers faced by people with disabilities. The results indicate that practical activities provided greater awareness of inclusion: 83% of participants reported being better prepared to apply academic knowledge in real contexts, and 76% observed the development of interpersonal skills, such as empathy and collaboration. In addition, 92% of students highlighted a broader understanding of social and environmental issues. These findings reinforce the curricularization of extension as an essential political-pedagogical project for the formation of critical and engaged citizens. In response to the National Education Plan and Resolution No. 7/2018, the study highlights the relevance of extension practices as a central part of the academic curriculum, contributing to a more inclusive and transformative higher education. DOI: https://doi.org/10.56238/sevened2024.037-155